Effect of temperature and fiber type on impact behavior of thermoplastic fiber metal laminates. (1st September 2019) - Sarasini, Fabrizio; Tirillò, Jacopo; Ferrante, Luca; Sergi, Claudia; Sbardella, Francesca; Russo, Pietro; Simeoli, Giorgio; Mellier, David; Calzolari, Andrea
Abstract: Thermoplastic fiber metal laminates (TFMLs) represent a relatively new class of fiber metal laminates (FMLs) specifically designed to overcome the limitations of conventional fiber metal laminates in terms of the elevated processing temperatures and pressures required for their consolidation. In this work the low velocity impact response of TFMLs based on aluminum alloy and a polypropylene (PP) matrix reinforced with basalt fibers has been experimentally addressed, by considering the effect of the stacking sequence and of the impact temperature. The results have been compared with those obtained on glass fiber/PP reinforced FMLs, basalt/epoxy reinforced FMLs and monolithic aluminum. Basalt TFMLs showed a better performance than aluminum plates, basalt/epoxy TFMLs and glass TFMLs, especially for the specific energy level causing FC (first crack), with an increase of 42%, 34%, 8.5% respectively due to a greater deformation ability of basalt fiber metal laminates even at an impact temperature as low as −40 °C.